DAMPAK INTEGRASI EKONOMI ASEAN TERHADAP PERDAGANGAN INDONESIA PADA SEKTOR KENDARAAN RODA EMPAT - K. Dianta A. Sebayang (Jurnal Ilmiah Econosains, 2011)
ABSTRACT This study aims to determine the significane of economic integration to Indonesia trade between ASEAN countries, especially the vehicle sector since ASEAN FREE TRADE AREA (AFTA) between 1991-2006. The methodology used is the Gravity model which often used to analyze bilateral trade, the effects of liberalization and trade agreements. The population in this study are the most dominant Indonesia trading partners at the four-wheeled vehicle, which are Malaysia, Philippines, Thailand, and Singapore, as the ASEAN members, and as comparison Australia, South Korea, Japan and the United States as non ASEAN members. The results showed that based on the estimation results, AFTA has a significant impact to Indonesia four-wheeled vehicle trade. The results of this study is expected to be uses as a reference for policy makers of ASEAN members and the private sector, especially Multi National Company (MNC) to formulated policy which are more efficient and effective on the automotive sector among ASEAN members.Keywords: economic integration, the Gravity model, AFTA